Pengaruh Intellectual capital, Environmental performance, Green innovation, dan Financial flexibility terhadap Sustainable growth - Regina Jansen Arsjah; Tyas Handayani (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study aims to test and analyze the effect of intellectual capital, environmental performance, green innovation, and financial flexibility on sustainable growth. The data used in this study are secondary data obtained from financial reports, annual reports, and sustainability reports of companies in the non-cyclical consumer sector listed on the Indonesia Stock Exchange for the period 2020–2022, which obtained an environmental performance assessment from the Ministry of Environment and Forestry of the Republic of Indonesia. The sample of this study consisted of 97 companies. This research was processed using the regression analysis method using EVIEWS 12. The results of the analysis show that intellectual capital has a positive effect on sustainable growth. However, environmental performance, green innovation, and financial flexibility have a negative effect on sustainable growth.